DIDACTICAL DESIGN RESEARCH BASED REFLECTION PRACTICE IN TEACHER PROFESSIONAL DEVELOPMENT - Vici Suciawati; Sudianto Sudianto; Mohamad Gilar Jatisunda; Iik Nurhikmayati (LPM Universitas Pasundan, 2021)
Reflection practice is a form of teacher professional development activity that has become the focus of study, research, and discussion in several scientific forums. The practice of reflection used so far is lesson study and educational action research. Didactical design research is one form of educational design research. DDR for mathematics teachers has been widely developing in Indonesia, both at the elementary, junior high, and high school levels. This service program begins with an introduction to Didactical Design Research. Form and its characteristics of didactical design research provide through a zoom meeting, and it will continue with the creation and development of a didactic design for learning mathematics based on the problems faced by the teacher. After the participants' activities, especially teachers, based on the results of the questionnaire response analysis of knowledge and understanding related to the concept of didactical design research, then the practice of reflection based on didactical design research increases and is ready for a workshop.